2017
DOI: 10.1177/1010428317699117
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic perturbation of epigenome by inhibiting S-adenosylhomocysteine hydrolase elicits senescence through DNA damage response in hepatoma cells

Abstract: Cellular senescence is a key physiological barrier against tumor and represents an option for therapeutic intervention. One pivotal intracellular stimulus causing senescence is DNA damage response, while the senescence-associated heterochromatin in cancer limits the strength of the DNA damage response to endogenous genotoxic stress or DNA-damaging agents. Therefore, targeting the maintenance of compacted chromatin in cancer cells represents an optional intervention to improve the therapeutic efficacy in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Mechanistically, we demonstrated that DZNep induced apoptosis without inducing γH2AX, a biomarker for DNA damage [23]. Similar observations was done in other studies [7,24], while another study reported that DZNep increases γH2AX in hepatoma cells [25]. Interestingly, we identified EGFR as putative mediators of DZNep induced-apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…Mechanistically, we demonstrated that DZNep induced apoptosis without inducing γH2AX, a biomarker for DNA damage [23]. Similar observations was done in other studies [7,24], while another study reported that DZNep increases γH2AX in hepatoma cells [25]. Interestingly, we identified EGFR as putative mediators of DZNep induced-apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…4A ) suggested a significant increase in double-stranded DNA breaks, which is in agreement with the immunoblotting results that indicate the activation of the protein kinase ATM within the DDR signalling cascade. Other studies show possible connections between AHCY and DNA damage; however, the approaches were based on small molecule inhibitors of AHCY 20 , 35 .
Figure 4 yH2AX spread analysis.
…”
Section: Resultsmentioning
confidence: 99%
“…Based on these reports, the involvement of AHCY in the molecular mechanisms of cancer is undisputable. Recently, AHCY-driven mechanisms have been discussed, such as the treatment of liver carcinoma cells (HepG2) with AHCY inhibitors, where the DNA damage response is predicted to be enhanced by endogenous genotoxicity due to DNA damage and subsequent perturbation of the cellular epigenome 20 ; however, the mechanisms by which AHCY affects cancer are still elusive. Additionally, in regard to research on HepG2, most studies evaluated the genotoxicity of many direct and indirect mutagens and compounds with unknown or poorly known mechanisms of action 21 24 , thus leaving many questions unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the analysis in DAVID, Hyper-LGs in HCC, GO enrichment analysis demonstrated BP included response to endogenous and hormone stimulus, cell surface receptor linked signal transduction, and behavior. One fundamental endogenous genotoxic stimulus could cause DNA damage response in cancers[ 19 ]. MF enrichment indicated glycosaminoglycan, pattern and polysaccharide binding, and protein tyrosine kinase activity.…”
Section: Discussionmentioning
confidence: 99%